A realist evaluation of a multi-component program with disengaged students - Emily Owen (Evaluation and Program Planning, 2024)
Periods spent in the absence of education, employment, or training (NEET) are associated with adverse psychological wellbeing, social marginalisation, and premature mortality. Implementing effective programs to re-engage young people who are classified, or are at risk of becoming NEET, is of importance to these individuals, family, and society. We conducted a realist evaluation to understand how, and under which circumstances a multi-component program may impact the engagement, behavioural, and psychosocial outcomes of disengaged students at risk of becoming NEET. During the early project phase, a narrative review of the literature and key stakeholder discussions were conducted to develop our initial program theories regarding how the program was expected to achieve its outcomes. Participant observations, video footage, and forty-two interviews were then conducted with teachers and students to form context-mechanism-outcome configurations and to refine these theories. Overall, refined program theories relating to positions of authority, the power of collective experience, exploration of possible life directions, constructivist pedagogies and active learning, and the endorsement of an ethic of caring and strengths-based orientation were developed. Collectively, our findings provide a detailed understanding of the architecture of programs that may benefit disengaged students and help inform the design of future programs aimed at reducing disaffection.